Shall We Sanctify Ourselves with Biomedical Technology? A Reformed Appraisal of Moral Bioenhancement - Xu, Ximian (Theology and science, 2024)
This paper attempts to develop a constructive dialogue between moral bioenhancement and Reformed theology of sanctification. According to Reformed theology, human beings are first sanctified by God objectively (passive sanctification) and consequently seek subjectively for their own growth in moral life (active sanctification). Moral bioenhancement and sanctification, thus, share a commonality, that is, emphasizing moral betterment. As such, to the extent that passive sanctification is not obliterated but rather prioritized, moral bioenhancement can be viewed as a consequence of a good work performed freely by the sanctified person to seek for moral growth in the imitation of Christ.